Prevalencia del estreptococo beta hemolítico en gestantes de 35 a 37 semanas en el Hospital UTPL durante el periodo septiembre 2011 – septiembre 2012. - Sánchez Díaz, Eddy Patricio (2014)
Researcher: Sánchez Díaz, Eddy Patricio. • Director: Astudillo Romero, Ernesto Xavier, Dr. • Location of intervention: UTPL Hospital; Loja, Ecuador. • Intervention Period: September 2011 to September 2012. • Primary objective: Determinate the prevalence of betahemolytic streptococcus and associated risk factors in pregnant women of 35-37 weeks to the obstetrics and gynecology service at UTPL Hospital. • Type of study: Analytical, quantitative and cross design approach • Methodology: Culture of vaginal and rectal sample (screening) and observation data sheet prepared according to the objectives. Microsoft Office Excel 2007® the program was used for the tabulation of the data collected. • Universe: pregnant women presenting for antenatal care at UTPL Hospital. • Sample: All pregnant women 35 to 37 weeks who presented to obstetrics and gynecology service at UTPL Hospital during the period September 2011 to September 2012 and who met the inclusion criteria (gestational age, study period and consent) • Results: The prevalence of beta hemolytic streptococcus in pregnant women from 35 to 37 weeks in the Hospital UTPL is 12.96%. The secondary risk factors were associated with the presence of urogenital tract infection in pregnancy, first sexual intercourse earlier and with more than one sexual partner compared to negative patients at screening. Factors such as marital status, education, occupation, place of residence, number of previous abortions and deeds, not associated with higher prevalence. The data regarding prevalence and risk factors are similar to those of other studies in the country patterns.